A critical review of the potential impacts of marine seismic surveys on fish & invertebrates. Issue 1 (15th January 2017) - Carroll, A.G.; Przeslawski, R.; Duncan, A.; Gunning, M.; Bruce, B.
Abstract: Marine seismic surveys produce high intensity, low-frequency impulsive sounds at regular intervals, with most sound produced between 10 and 300 Hz. Offshore seismic surveys have long been considered to be disruptive to fisheries, but there are few ecological studies that target commercially important species, particularly invertebrates. This review aims to summarise scientific studies investigating the impacts of low-frequency sound on marine fish and invertebrates, as well as to critically evaluate how such studies may apply to field populations exposed to seismic operations. We focus on marine seismic surveys due to their associated unique sound properties (i.e. acute, low-frequency, mobile source locations), as well as fish and invertebrates due to the commercial value of many species in these groups. The main challenges of seismic impact research are the translation of laboratory results to field populations over a range of sound exposure scenarios and the lack of sound exposure standardisation which hinders the identification of response thresholds. An integrated multidisciplinary approach to manipulative and in situ studies is the most effective way to establish impact thresholds in the context of realistic exposure levels, but if that is not practical the limitations of each approach must be carefully considered. Highlights: Generalisations about impacts are often inappropriate due to the vast gap in our knowledge about sound thresholds and recovery from impact. A disparity exists between results obtained in the field and results obtained from the laboratory. A multidisciplinary approach to lab & field studies is ideal, but if not practical, the limitations of each approach must be carefully considered.